Studies of late sarmatian mounds on the Koksengir plateau (based on archival materials of the Khorezm archaeological and ethnographic expedition) (Journal of history, 2023)
The article provides an overview of the results of archaeological research of the Khorezm Archaeological and Ethnographic Expedition (KhAEE) conducted in the Eastern Aral Sea region in the 40-90 years of the XX century. In addition, we consider the burial mounds of the Koksengir plateau, which were explored by the Khorezm expedition in 1960-1961.When studying the archaeological source, traditional methods were used, combining field and laboratory studies. The source base of the research consists of the materials of the KhAEE, stored in the archival fund of the Miklukho-Maklay Institute of Ethnology and Anthropology of the Russian Academy of Sciences, and the published works of members of the Khorezm and Chirikrabat archaeological expeditions.The publication publishes for the first time some archives of the KhAEE. For example, the results of the excavations carried out in mounds No. 2 and No. 3, and a color photograph of the lining with the image of a golden camel's head attached to the scabbard of a sword found in mound No. 1 have been preserved only in the archive. Also, under the leadership of A.A. Tazhekeyev, repeated exploration work was carried out in the area of the location of the research object.Science knows that the materials of the Sarmatian period along the lower course of the Syr Darya can be found in the sites of the Zhetyasar tract. However, as a separate Sarmatian site, only the Koksengir mounds can be mentioned so far. Therefore, we believe that these articles are important for Sarmatian archaeology.The article was prepared as part of the implementation of the program-targeted funding of the Ministry of Science and Higher Education of the Republic of Kazakhstan on the topic: "The Hunno-Sarmatian era in the history of Kazakhstan: interdisciplinary research, analysis and reconstruction" (registration number: BR 18574175)Keywords: Syr Darya, Khorezm archaeological and ethnographic expedition, Koksengir, mounds, ceramics.